AHAMIYYAH AL-LUGHAH AL-‘ARABIYYAH FI BINA' WA TATHAWWUR AL-MUJTAMA‘ - Ammar Madi (Afshaha: Jurnal Bahasa dan Sastra Arab, 2024)
Arabic language has a glorious history. It has maintained its existence for centuries, and it has not weakened or aged. This study aims to examine the role of the Arabic language in the formation and development of society. Using a descriptive-qualitative approach, this research analyzes the existence of the Arabic language in meeting the social, cultural, and psychological needs of its speakers over time. The results show that the Arabic language has endured for centuries while remaining adaptable to the advancements of the era. It has evolved through various historical phases without losing relevance and has absorbed new elements from the civilization of its speakers. Arabic continuously develops through the renewal of its structures and vocabulary to accommodate the communicative needs of its community. As a dynamic social and cultural phenomenon, the Arabic language is closely connected to the nation of its speakers, influenced by its systems, traditions, and progress. Thus, this study confirms that the Arabic language is a living entity that continuously adapts to support the advancement of Arab society.